Critical impact energy for local impact damage of hard projectile on concrete slab - Bux @ Imran Latif, Qadir (2012)
Concrete is a common construction material used to build conventional, unconventional, and sensitive structures. Great demand exists for efficient designing of concrete as protective structures against impact loading generated by natural disasters and consciously engendered unpleasant incidents etc. When hard projectile collides with concrete wall it is the impact energy of the projectile that makes concrete target to deform, which means impact energy is the dominant cause of damage in impact accidents. Hard missile impact can generate both local (penetration, scabbing, and perforation) and global impact damage. Local damage studies normally fall into three categories, i.e. empirical formulation, idealised analytical models, and numerical simulations. The present study is curiously focused on the required critical impact energy for occurrence of local impact damage in concrete structures generated by hard projectile, via three categories i). Numerical simulation, ii). Analytical modelling, and iii). Empirical formula The numerical simulations were conducted to determine the critical impact energy of ogive nose hard projectile which causes maximum penetration in to the concrete structures. The effects of diameter and CRH ratio of ogive nose hard projectile on critical impact energy were also analysed. An analytical model is developed to predict the required critical impact energy for spalling, tunnelling and penetration in concrete target. A nose shape factor (Ni) also has been introduced with empirical friction factor (Nf) in Chen and Li nose shape factor (N* ), to analyze the effects of nose shape on critical impact energy. Furthermore, an empirical formula also has been developed. The early stage scabbing phenomenon has been observed through the wave propagation in simulations with fully elastic model assumptions. The critical impact energy required for scabbing of concrete target and the effects of diameter of projectile (d) and the target thickness (H) on critical impact energy has been observed. An analytical model is developed based on 1-Dimensional with reflected wave propagation, and shear assumptions. Furthermore, an empirical formula also has been introduced. For perforation, the penetration numerical simulations have been further extended to achieve perforation in deep concrete against impact of ogive nose hard projectile with CRH = (3.0, 4.25, and 6.0). The required critical impact energy and residual impact energy has been analysed. Furthermore, the modifications in Li and Reid (2006) perforation model also have been done. In Addition a new empirical formula also has been introduced. The out come of this study can be used for making design recommendation and design procedures for determining the dynamic response of the concrete target to prevent local impact damage